A LINGUISTIC ODYSSEY: UNCOVERING LANGUAGE’S EVOLUTIONARY STORY - Al-Mansoori, Amir Hussein; Al-Khateeb, Fatima Abdullah (Top Linguistic and Language Journal (TLLJ), 2023)
The study of language and its various branches has been the subject of much debate and speculation among researchers and scholars. From the emergence of language to its current diversity, many theories have been proposed, yet the answers to fundamental questions such as how language began and how it developed remain elusive. This paper aims to address some of these questions and provide a better understanding of the topic. Through a journey across human evolution, from the larks with flat nails to the present-day inventors, this paper explores the importance of language and its role in human communication and civilization. The study delves into the history of language and linguistics, examining the emergence and development of language in different regions of the world, including Asia. The research aims to reach some results by delving into the subject of language, which is difficult to study but also essential to understand human nature and the evolution of human society. The study of language helps us to understand how people communicate and interact with one another and how this interaction shapes human civilization. By providing a comprehensive analysis of the subject, this paper aims to contribute to the ongoing research in the field of linguistics and the study of human evolution